2018
DOI: 10.1371/journal.pone.0202012
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of work endurance in disability evaluations across European countries

Abstract: PurposeChronic disease is often associated with a reduced energy level, which limits the capacity to work full-time. This study aims to investigate whether the construct work endurance is part of disability assessment in European countries and what assessment procedures are used. We defined work endurance as the ability to sustain working activities for a number of hours per day and per week.Materials and methodsWe conducted a survey using two self-constructed questionnaires. We addressed 35 experts from 19 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…A limitation of working hours due to chronic disease usually results in partial disability in the Netherlands. Also in other countries the assessment of the (in)ability to work fulltime is an aspect of work disability assessment, although there are differences between countries in used definitions and measures to assess this construct [16]. Overall, more research on this topic is warranted, taking into account the huge impact the assessment outcome can have both from societal and individual perspective [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…A limitation of working hours due to chronic disease usually results in partial disability in the Netherlands. Also in other countries the assessment of the (in)ability to work fulltime is an aspect of work disability assessment, although there are differences between countries in used definitions and measures to assess this construct [16]. Overall, more research on this topic is warranted, taking into account the huge impact the assessment outcome can have both from societal and individual perspective [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In many European countries, inability to work fulltime is recognized as an important concept in work disability assessments [2]; the concept includes the restricted number of hours per day or week a claimant is able to work due to a chronic disease and/or other accepted causes. A previous study comparing 16 European countries showed that a majority of them included assessment of inability to work fulltime (or restricted work endurance) as part of the work disability assessment [2]. If a person is not able to work fulltime it can be described as an inability to work fulltime.…”
Section: Introductionmentioning
confidence: 99%
“…If a person is not able to work fulltime it can be described as an inability to work fulltime. Across countries, the definition of fulltime ranged from 35 to 42 h per week [2]. Both physical and mental disorders are accepted causes of inability to work fulltime, with the most often mentioned causes being musculoskeletal diseases, mental disorders, and diseases of the circulatory system.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations